Biodegradation of Plastics using Bacteria Isolated from Wastes Dumping Soil within Sokoto Metropolis - Aisha Bashir; Aminu Yusuf Fardami; Ibrahim Yusuf Tafinta; Umar Balarabe Ibrahim (UMYU Journal of Microbiology Research)
Study’s Excerpt: